2015
DOI: 10.1090/conm/641/12859
|View full text |Cite
|
Sign up to set email alerts
|

Left-Induced Model Structures and Diagram Categories

Abstract: Abstract. We prove existence resultsà la Jeff Smith for left-induced model category structures, of which the injective model structure on a diagram category is an important example. We further develop the notions of fibrant generation and Postnikov presentation from [9], which are dual to a weak form of cofibrant generation and cellular presentation. As examples, for k a field and H a differential graded Hopf algebra over k, we produce a left-induced model structure on augmented H-comodule algebras and show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…Most recently Drummond-Cole and Hirsh applied the main theorem of [4] to establish the existence of a poset of model category structures on categories of coalgebras over coaugmented, weight-graded cooperads in the category of chain complexes, either unbounded or bounded below, over a field, where the weak equivalences and cofibrations are created by the cobar construction associated to a twisting morphism [12]. Their work generalizes results of Vallette for Koszul cooperads [43].…”
Section: Coalgebras Over Cooperadsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently Drummond-Cole and Hirsh applied the main theorem of [4] to establish the existence of a poset of model category structures on categories of coalgebras over coaugmented, weight-graded cooperads in the category of chain complexes, either unbounded or bounded below, over a field, where the weak equivalences and cofibrations are created by the cobar construction associated to a twisting morphism [12]. Their work generalizes results of Vallette for Koszul cooperads [43].…”
Section: Coalgebras Over Cooperadsmentioning
confidence: 99%
“…Let H be a bimonoid in Ch R , and consider Alg H R , the category of H-comodules in the category of Alg R of differential graded R-algebras. In [4,Theorem 3.8] it was shown that if R is a field, and H is of finite type and non-negatively graded, then the category of non-negatively graded H-comodule algebras (Alg + R ) H admits a model category structure left-induced from the model category structure on Alg + R that is right-induced from the projective structure on Ch R . Here we generalize this result to any commutative ring and any bimonoid H, at the price of working with chain homotopy equivalences rather than quasi-isomorphisms as our weak equivalences.…”
Section: Comodule Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…. , [3], and let sSet 3 = [∆ op 3 , Set]. Left Kan extension, restriction and right Kan extension along the inclusion ∆ 3 ⊆ ∆ gives a chain of adjoints sk 3 tr 3 cosk 3 : sSet 3 → sSet with both sk 3 and cosk 3 fully faithful.…”
Section: Examplesmentioning
confidence: 99%
“…Earlier work on special cases of model structures on categories of coalgebras can be found in [14], [2], and [13], among others.…”
mentioning
confidence: 99%